Direct saliva transcript analysis as a novel non-invasive method for oestrus marker detection in buffaloes. (17th February 2016) - Onteru, Suneel Kumar; Baddela, Vijay Simha; Ravinder, Ravinder; Kaipa, Onnureddy; Nayan, Varij; Singh, Prashant; Baithalu, Rubina Kumari; Singh, Dheer
Abstract: Salivary RNA-based biomarkers are not available for any physiological condition in farm animals. Hence, an objective of this study was to perform salivary transcript analysis in buffaloes. Saliva, after removal of the cells and particulate matter, was directly used for RT-PCR without RNA isolation. Direct saliva transcript analysis (DSTA) showed a suggestively significant higher expression of the Heat shock protein 70 ( HSP70 ) and Toll-like receptor 4 ( TLR4 ) at oestrus than the diestrous period in buffaloes by a non-parametric Mann-Whitney U test. Therefore, DSTA without RNA isolation is an easy method to identify salivary RNA markers for oestrus detection in buffaloes.